1999
DOI: 10.1051/rnd:19990101
|View full text |Cite
|
Sign up to set email alerts
|

Development of gastrointestinal and pancreatic functions in mammalians (mainly bovine and porcine species): influence of age and ingested food

Abstract: -This review summarizes recent advances in knowledge on the development of digestive tissues and their productions as well as mechanisms of regulation in response to age and ingested food in mammalian species (mainly bovine and porcine species). In the first two sections, changes are reported for stomach, pancreas and small intestine, and examined in relation to different situations (colostral, milk feeding and weaned periods). The implication of some regulatory substances (growth factors, gut regulatory pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 67 publications
(97 reference statements)
1
23
0
Order By: Relevance
“…The development of the pancreas starts in the prenatal period, and in general, the activity of pancreatic enzymes in tissue homogenates increases with fetal age up to birth. However, it is after birth when there is a positive allometry and an isometry of the pancreas associated with age (Lindemann et al, 1986;Zabielski et al, 1999), and based on DNA and RNA measurements in the pancreas, Corring et al (1978) ascribed the increase in pancreas weight before 4 wk of age to a hyperplasia of pancreatic cells; subsequent increases involve both hyperplasia and hypertrophy. Lindemann et al (1986) elegantly showed the ontogenic development of lipase, amylase, chymotrypsin, and trypsin activity of the pancreas from birth to 6 wk of age, with activity (expressed either per gram of pancreas or total activity) increasing linearly to weaning, decreasing in the week after weaning, and then (except for lipase) increasing dramatically thereafter in response to dietary substrate associated with the change from milk to a predominately plant-based diet.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The development of the pancreas starts in the prenatal period, and in general, the activity of pancreatic enzymes in tissue homogenates increases with fetal age up to birth. However, it is after birth when there is a positive allometry and an isometry of the pancreas associated with age (Lindemann et al, 1986;Zabielski et al, 1999), and based on DNA and RNA measurements in the pancreas, Corring et al (1978) ascribed the increase in pancreas weight before 4 wk of age to a hyperplasia of pancreatic cells; subsequent increases involve both hyperplasia and hypertrophy. Lindemann et al (1986) elegantly showed the ontogenic development of lipase, amylase, chymotrypsin, and trypsin activity of the pancreas from birth to 6 wk of age, with activity (expressed either per gram of pancreas or total activity) increasing linearly to weaning, decreasing in the week after weaning, and then (except for lipase) increasing dramatically thereafter in response to dietary substrate associated with the change from milk to a predominately plant-based diet.…”
Section: Figurementioning
confidence: 99%
“…All components and accessory organs of the GIT are influenced by weaning, irrespective largely of weaning age; however, because of its size and biological importance, it is the small intestine that is affected the most and has to make the greatest anatomical, physiological, and immunological adaptation to changes in the pattern and form of feed consumption, changes in dietary substrates, and adjustment to stress (e.g., Stokes et al, 1994;Cranwell, 1995;Xu, 1996;Pluske et al, 1997;Zabielski et al, 1999;Burrin and Stoll, 2003;Pluske et al, 2003;Boudry et al, 2004;Lallès et al, 2004;Burkey et al, 2009;Wijtten et al, 2011Wijtten et al, , 2012Pluske, 2013). It is simply beyond the scope of this review to summarize all the changes to the GIT that occur in the periweaning period, with a plethora of authors having already described the rapid and consistent changes to structure (e.g., villous height and crypt depth, size and shape, tight junction integrity) and function (e.g., digestive and absorptive activity and capacity, loss of surface area, inflammation, antioxidant capacity) that occur in the acute and adaptive phases of growth in the periweaning period (Fig.…”
Section: Changes To the Structure And Function Of The Git After Weaningmentioning
confidence: 99%
“…In some mammals at weaning, a second period of growth occurs, but, the majority of experimental evidence indicates that dietary changes at weaning modulate levels of enzyme activity rather than initiate intestinal changes [12,16,20]. In cats, the majority of changes within the gastric mucosa appear during the neonatal period [34]; literature suggesting that the age related changes in apparent digestibility coefficients observed in this study are more probably due to dietary modulation of enzyme expression rather than maturation of the gastro-intestinal tract. Gut enzyme biochemistry data, and pre-weaning or at weaning apparent digestibility coefficients would be required in order to exclude diet as the major driving force behind the improving apparent digestibility coefficients.…”
Section: Age and Digestibilitymentioning
confidence: 99%
“…There is substantial evidence to support a protective role for dietary fi bers against colorectal cancer [3,5] . Several studies on the consequences of legume consumption have clearly demonstrated that it increases the mass of the digestive content and of the digestive tissues themselves [6,7] . However, more knowledge is needed to understand group was pair-fed with an iso-energetic, iso-nitrogenous balanced casein diet.…”
Section: Introductionmentioning
confidence: 99%